PERLINDUNGAN HUKUM TERHADAP TERSANGKA YANG MENDAPATKAN KEKERASAN DALAM PROSES PENYELIDIKAN DAN PENYIDIKAN DI POLRES TENGGARONG - Setiadi, Wahyu (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTThe suspect is faced with a public prosecutor before the court, both of whom have the same position, including their rights. The public prosecutor will try to provide evidence to the court that can convince the judge that the suspect is guilty and deserves a sentence. Whereas the suspect himself has the right to deny what he has been accused of by showing evidence, even what he has been accused of is not true. If the suspect cannot prove that he is innocent, the criminal proceedings against the suspect will continue until the final stage.If there has been a violation of his rights by the investigator, the suspect can do something that can make the investigator concerned must account for his actions. Legal remedies that can be submitted by a suspect, his family and legal counsel are pre-trial efforts.The obstacle faced in providing legal protection is that the existing legal regulations are not yet fully implemented and the sociological regulations do not apply in the community. In addition, because of the attitude of the defendant himself who cannot be invited to work together. The lack of available facilities and infrastructure as well as the lack of funds to conduct investigations and investigations also led to the difficulty of upholding the rights of suspects. There is still a lack of supervision and control when the examination takes place, so as to make the investigator freely carry out the examination by himself according to the method he likes.